Present Situation of the Internal Quantitative Efficiency of Sanhan Community College - the Republic of Yemen - Mohammed Zain Saleh AL Sadi; Nasser Saeed Ali Aldahyani (University of Science and Technology, Yemen, 2017)
The research aimed to explore the present situation of the internal quantitative efficiency of Sanhan community college, and to identify the annual cost per student and material waste resulting from failure and dropout. The study depended primarily on the method of restructuring the study life in order to measure the internal efficiency of quantitative indicators for the college.  This was done by building the chart structure of student flow, which allows calculating success rate, failure rate, and the dropout rate for each batch. This enabled the researchers to calculate the indicators of internal quantity efficiency and its level. The study results revealed that the educational system in Sanhan Community college has not reached the required standard, which impacted  the internal quantitative efficiency. In addition, the proportion of quantitative loss resulting from students' failure and dropout was (50%). Some recommendations were also proposed in order to raise the efficiency and effectiveness level so as to reach the desired standard. Keywords: Internal quantity efficiency, Sanhan Community College, Yemen.